Re-Discovering & Re-Conceptualising Local Area Plans: A Qualitative Investigation in Guiding Spatial Sustainability in Maitland, Cape Town - Messaris, Anastasia (School of Architecture, Planning and Geomatics, 2023)
Cities and their sub-units are increasingly conceived as being dynamic, relational, and unbounded. Due to these attributes, they are recognised as a key means of driving sustainability and sustainable urban development (which is best understood as the entwined requirements for progress towards lasting wellbeing). In response to this, the global policy document the New Urban Agenda Illustrated introduced a fourth dimension to sustainable urban development: spatial sustainability, wherein guiding the physical form of urban environments towards specific spatial conditions can enhance social, economic, and environmental value and wellbeing and, in so doing, arrive at equity. The document recommends the use of local area plans to guide urban development toward spatial sustainability. However, South Africa's local area plans are currently not conceptualised to guide spatial sustainability which, as a recent global concept, has yet to be rigorously researched in specific contexts. Moreover, local area plans are generally under-explored and under-utilised in South African planning theory and policy, where the emphasis is on large-scale strategic spatial plans and spatial development frameworks. In response to this, the research aims to 1) establish whether South Africa's planning system requires local area plans and, if so, to clarify their contribution, and 2) to enrich the interpretation of spatial sustainability, with the view to 3) exploring how planners might re-discover and re-conceptualise local area plans to guide spatial sustainability. The research aims were achieved through the qualitative research approach that methodologically made use of a case study in Maitland, Cape Town. Data was collected and analysed through various techniques and against a conceptual framework derived from a literature review. The study employed design-orientated inquiry in which an initial local area plan proposal was presented to a focus group and – based on their feedback – undetected facets of analysis were further explored and the local area plan proposal was redrafted. The enriched interpretation of spatial sustainability recognises that space that seeks to achieve equity comprises relations and processes as much as the substantive features of physical form. To this end, the research suggests that it is necessary to appreciate the context, structure, and dynamics of place (the product of planned space), which is best understood through analysing the activity, psychology, and physicality of place. The results of this analysis in Maitland are threefold. Firstly, the analysis confirms that local area plans are a crucial component of South Africa's planning system when situated in areas of strategic importance. Secondly, Maitland is revealed to be a multifaceted port-of-entry neighbourhood where relations and practices extend beyond the area's boundaries. Thirdly, the results suggest that a local area plan re-conceptualised to guide spatial sustainability should be viewed as both a process and a product. In other words, local area planning requires two responses: it needs to produce a material local area plan (the plan as a noun), and the method of achieving that plan needs to foster the conditions for diverse current and future involvement in the planning process (planning as a verb). Based on these significant findings and using Maitland as a point of reference, the research proposes recommendations for preparing for, producing, and sustaining a local area plan in areas of strategic importance. Re-discovered and re-conceptualised in this way, local area plans are an essential means of achieving equity and lasting wellbeing in complex contemporary contexts, which is the fundamental objective of spatial sustainability.